Ethno-Regionalism And Political Party Loyalty In The Gambia: A Fracture In The Newly-Found-Democracy (European Journal of Behavioral Sciences, 2021)
This article interrogates what inspires the resurgence of ethno-regional political party loyalty in contemporary Gambian politics. It explores the relationship between ethnicity/regionalism and political party affiliation and the possible impact of ethnic politics on ideal democratic ethos and development in the small West African state. The article demonstrates how people sought security to reduce the uncertainty they face in a seemingly competitive and hostile world through the invocation of firm lost values as a way to rebuild a life in which they can achieve emotional and perhaps, physical safety. The study adopts a qualitative method of data collection, using a purposive sampling technique to select a sample size of 30; it relied extensively, inter alia, on the use of primary data obtained from the Independent Electoral Commission (IEC) The Gambia, and as well as secondary data sources. The study reveals that ethno-regionalism continues to influence partisan loyalty and thus electoral outcomes in The Gambia. It further reveals that the turbulent pre and immediate post-2016 Presidential election of The Gambia resulted in ethnic motivated political party loyalty, fear of violent reprisals, and accusatory rhetoric. This in a way, resulted from political elites' exploit of people's ethnic consciousness in an attempt to oust President Jammeh in 2016. The split-over effect of this continues to jeopardise the corporate existence of various identities in the country and strain efforts to build a peaceful, harmonious, and prosperous Gambia.